Load frequency control considering energy storage system - Lee, Yong De (Nanyang Technological University, 2024)
The integration of renewable energy sources into the power grid poses considerable issues in terms of frequency stability due to their inherent intermittency. Traditional Load Frequency Control (LFC) systems, which rely on traditional generating technologies, sometimes struggle to handle rapid swings in power supply and demand. This Final Year Report investigates the unique use of Energy Storage Systems (ESS) in LFC to improve grid reliability and performance. By utilizing the quick response capabilities and flexibility of ESS, we offer an enhanced LFC framework that dynamically balances load and frequency, minimizing the implications of renewable energy variability. Through extensive simulation and analysis, the research reveals how ESS may effectively support LFC by providing immediate power reserves, lowering reliance on fossil fuel-based ancillary services, and supporting a more sustainable energy infrastructure. The findings highlight the potential of ESS-enhanced LFC in building a resilient and efficient power grid, paving the path for greater use of renewable energy and a more sustainable future.